Design and build a turbochanger stand and airflow circuit piping for an automotive turbochanger testing apparatus - Mohammad Iskandar, Othman (2008)
Development in automotive technology sector creates a new idea in turbocharger system. The tasks given for the final year project is to the design and builds a turbocharger stand and airflow circuit piping for an automotive turbocharger testing apparatus. The airflow piping was made using PVC pipe. The piping made from the blower to the compressor inlet. Compressor outlet piping was branched into two; flow through an intercooler and flow bypass the intercooler. Meanwhile, the flow into and out from the turbine was also installed in the apparatus. Variable speed blower is used to supply incoming air to the turbo compressor. This test apparatus was far from complete as this is the first step to a complete instrumented turbocharger test apparatus that capable of measuring input and output pressure and temperature.